Sistem Pengunci Otomatis Terrarium Reptile Dengan Kendali Aplikasi Finger Print Berbasis Arduino - Eka Kusuma Pratama (Jurnal Ilmiah Teknologi Informasi Asia, 2020)
ABSTRACT. As time progressed also a new Hobby in the community such as the Hobby Reptile or better known as Reptiler. Many pure reptilers have been maintaining several types of dangerous or high-quality animals, some of which only follow the trend or are currently viral. Because of the ease of access to video sharing or photos in various social media applications leads to a high sense of ignorance and follow the trend that is being viral today. Unfortunately, many new reptilers only follow the trend but do not understand the risk of danger arising with many of its victims from the bite of some kind of rattlesnake this time lately. So that in the future no casualties arise due to Reptiler's hobbies that maintain different types of dangerous animals it is necessary that a double security method is able to help reduce the risk in the hobby. Prototype starts with the creation of a terrarium with a Microkontoler-based auto-lock, which is made up of several components i.e. Arduino UNO, Bluetooth module HC-05, Relay, Solenoid Lock and Android smartphone (including fingerprint) As an integrated automatic key controller using the Arduino as a controller.